Arsenic accumulation in lettuce (Lactuca sativa L.) and broad bean (Vicia faba L.) crops and its potential risk for human consumption. Issue 1 (January 2019) - Yañez, L.M.; Alfaro, J.A.; Avila Carreras, N.M.E.; Bovi Mitre, G.
Abstract: Exposure to arsenic (As) is considered one of the primary health risks humans face worldwide. This study was conducted to determine As absorption by broad beans and lettuce crops grown in soil with As contents and irrigated with water contaminated with this toxic element, in Pastos Chicos, Jujuy (Argentina). Total dry biomass (TDB) and total As were determined in soils, roots, leaves, pods and seeds. These data were used to determine several parameters, such as translocation (TF) and bioconcentration (BCF) factors, target hazard quotient (THQ), and carcinogenic risk (CR). Broad bean plants had the lowest biomass production when exposed to As in irrigation water and soil. Lettuce plants presented TDB reductions of 33.3 and 42.8% when grown in soil polluted with As, and in control soil under irrigation with contaminated water, respectively. The presence of this toxicant in broad bean seeds and lettuce leaves (edible parts) exceeded the limits established by Código Alimentario Argentino, i.e. 0.10 and 0.30 mg/kg, respectively. THQ values for lettuce leaves were higher than 1, the same as those for broad bean seeds when grown in soil with As contents and irrigated with arsenic-contaminated water, thus suggesting that consumers would run significant risks when consuming these vegetables. Furthermore, this type of exposure to As implied a CR that exceeded the acceptable 1 × 10 −4 risk level. Hence, we may conclude that consuming lettuce and broad beans grown at the evaluated site brings about considerable health risks for local residents.